The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/10790268.2018.1474692
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcome of non-surgical management of thoracic and lumbar spinal fracture-dislocations — a historical analysis in the era of modern spinal surgery

Abstract: Compared with historical non-surgical care, surgery for type C injuries decreases the chances of post-operative pain, late spinal deformity and also allowed early rehabilitation, once no bed restriction is necessary. Ethical issues based on this historical analysis may preclude performing a comparative study of non-surgical versus surgical management of these injuries in the modern spine era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Managing patients with complex posterior ligamentous injuries, like those with AO Spine type B or type C fractures, usually requires instrumented posterior fusion, as nonoperative management can lead to progressive kyphosis, increased pain, and potential neurological deterioration. 21 Palmisani et al 22 reported that MISS is generally used to treat type A fractures (more stable injuries), due to limitations achieving fusion using percutaneous screws or paraspinal approaches. Interestingly, the Wiltse approach provides a wider operative field than most MISS approaches, thereby allowing not only screw insertion but also better rod bending, along with the potential to correct kyphosis and indirect decompression, together with some room for posterior bone grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Managing patients with complex posterior ligamentous injuries, like those with AO Spine type B or type C fractures, usually requires instrumented posterior fusion, as nonoperative management can lead to progressive kyphosis, increased pain, and potential neurological deterioration. 21 Palmisani et al 22 reported that MISS is generally used to treat type A fractures (more stable injuries), due to limitations achieving fusion using percutaneous screws or paraspinal approaches. Interestingly, the Wiltse approach provides a wider operative field than most MISS approaches, thereby allowing not only screw insertion but also better rod bending, along with the potential to correct kyphosis and indirect decompression, together with some room for posterior bone grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Historical treatment of fracture-dislocation injuries with prolonged bed rest ( 10-13 weeks on average), generally results in residual deformity and pain syndromes. 33 Compared with modern case series, cases of fracture-dislocation, without neurological deficits, that are surgically treated generally have very satisfactory outcomes, most of the times with the patients returning to their normal activities. 33 Additionally, for patients with neurological deficits, some neurological improvement is documented, especially in those patients with incomplete spinal cord injuries.…”
Section: Discussionmentioning
confidence: 99%
“…33 Compared with modern case series, cases of fracture-dislocation, without neurological deficits, that are surgically treated generally have very satisfactory outcomes, most of the times with the patients returning to their normal activities. 33 Additionally, for patients with neurological deficits, some neurological improvement is documented, especially in those patients with incomplete spinal cord injuries. 8,31 Our review is limited, once it is based on results of case series and, thus, there is a lack of comparative treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations